ANALISIS KEKASARAN PERMUKAAN BAJA AISI 1045 PADA PROSES PEMESINAN BUBUT CNC DENGAN METODE TAGUCHI - Rahmat Dwi Cahyo; Muhammad Subhan; Indah Riezky Pratiwi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
In the manufacturing industry in the machining process especially CNC machining, the thing that must be considered is the level of surface roughness of the combination of parameters. This study aims to determine the minimum level of surface roughness in the CNC MORI SEIKI SL-25 machining process by setting the right machining process parameters. The machining process parameters analyzed were cutting speed, depth of cut and feeding. The experimental design is based on the Taguchi method and is an orthogonal matrix L9 (33) with 2 replications to overcome the interference parameters of the machining process. The analysis method in this experiment is the Taguchi method. Based on the results of the study showed that to reduce the variation of the response simultaneously, the cutting speed had the largest contribution of 36.50%, compared to the depth of cut which was 16.28% and feeding of -12.45%. Parameter settings that produce a minimum level of surface roughness are 150 m/min for cutting speed, 0.40 mm for depth of cut and 0.35 mm/put for feeding.